Mammary Hamartoma: A Narrative Review of a Rare Breast Disorder - Salati, Sajad Ahmad; Malik, Faiza Riaz (Lietuvos chirurgija, 2025)
Mammary hamartomas are rare, benign tumors that primarily affect women in their middle years. Tumor cells originating from native breast tissues are arranged in a disorderly way, which is their defining characteristic. In recent years, there has been a growing number of reports about them. A correlation between clinical, radiological, and histological findings is necessary to make the diagnosis. To raise awareness of this rare disorder and encourage medical professionals to take it into account when making a differential diagnosis of breast lumps, this review paper provides a brief overview of the epidemiology, pathogenesis, clinical presentation, investigations, and therapy of MH.